Analisis Penilaian Hasil Karya Berbahan Loose Part untuk Mengembangkan Higher Order Thinking Skills di TK Islam Bustanul Athfal Desa Sikanco Kec. Nusawungu Kab. Cilacap: Analysis of Loose Part Material Work Assessment to Develop Higher Order Thinking Skills at Bustanul Athfal Islamic Kindergarten, Sikanco Village, Nusawungu District, Cilacap Regency - Riyanto, Puji; Formen, Ali; Setiawan, Deni (ITScience (Information Technology and Science), 2024)
Technological developments require the younger generation to be creative and competitive; Loose Parts give children the freedom to be creative and explore; and PAUD institutions in Nusawungu District, Cilacap have switched from paper worksheets to utilizing loose parts. The study aims to analyze (1) Inhibiting factors and solutions for utilizing loose parts to improve higher order thinking (2) assessment techniques for children's work using loose parts to improve higher order thinking skills in Islamic Kindergarten (Bustanul Athfal) Sikanco Village, Nusawungu District, Cilacap Regency. This study is a field research with a qualitative approach. The data collection techniques used are interviews, observation and documentation. The data validity techniques used by researchers are source triangulation and method triangulation. Data analysis techniques include data reduction, data presentation and drawing conclusions. The conclusion of this study is the inhibiting factors and solutions for utilizing loose parts to improve higher order thinking skills in Islamic Kindergarten (Bustanul Athfal) Sikanco Village, Nusawungu District, Cilacap Regency. Nusawungu, Cilacap Regency is 1) Limited loose parts materials, the solution is the school will optimize the use of lost parts (add to the collection of loose parts materials). 2) Characteristics of children's abilities that have different HOTS achievements, the handling will adjust to the child's development achievements. 3) Limited time, the school will increase the duration of loose part activities. 4) Limited teacher knowledge, the school will hold human resource strengthening. 2) The assessment technique for children's work made of loose parts to improve higher order thinking skills in Islamic Kindergarten (Bustanul Athfal) Sikanco Village, Nusawungu District, Cilacap Regency is the Checklist technique, Assessment of Work Results and anecdotal notes.